ANALISIS PENDAPATAN USAHATANI KELAPA SAWIT PADA POLA MITRA DAN POLA SWADAYA DI KECAMATAN MARO SEBO ILIR KABUPATEN BATANGHARI - Putra, Rizky Anugrah Pratama; Mara, Armen; Saputra, Ardhiyan (Agripita Publisher, 2018)
This research aims to analyze the difference management and income of oil palm farming partner pattern and self-help pattern in Maro Sebo Ilir sub-district, Batanghari Regency. The location selection was done deliberately with the consideration that the Maro Sebo Ilir sub-district is one of the areas of oil palm plantation which has the highest productivity in Batanghari Regency and has two pattern of oil palm farming. The samples were taken by simple random sampling method with respondent as many as 82 farmers consist of 42 partner pattern farmers and 40 self-help pattern farmers. Data analysis using the method two different test average method calculate by SPSS software. The results show that there is a difference between management of oil palm farming partner pattern and self-help pattern that caused by the existence of coaching and intensive control of the company, land productivity and fresh fruit bunch (FFB) quality that owned by partner pattern farmers are better than land productivity and FFB quality that owned by self-help pattern farmers. Partner pattern farmers income is higher that self-help pattern, where the average income of oil palm farming in research area for partner pattern is Rp. 29.873.936/Ha/Year and total cost is Rp. 16.589.355/Ha/Year, while for self-help pattern farming, average income is Rp. 22.456.318/Ha/Year and total cost is Rp. 15.028.142/Ha/Year.